Jornalismo científico ou promoção institucional? análise das regularidades discursivas no jornalismo científico da UFMA, IFMA e UEMA - GOMES, Romulo Fernando Lemos (2013)
Discussion of the educational role of science journalism. Focuses attention on the exercise of journalistic communication advising of the largest institutions of higher education in Maranhão: Universidade Federal do Maranhão (UFMA), Instituto Federal de Educação, Ciência e Tecnologia do Maranhão (IFMA) e Universidade Estadual do Maranhão (UEMA). The objective is to investigate whether science journalism produced in public institutions achieves consistent educational purposes, to meet the training needs of scientific culture. Is taken as support for Social Theory of Discourse, Norman Fairclough (2001), who sees the speech as three dimensional: text, discursive practice and social practice. In an interview with heads of communications consultancies such institutions rose up the policies to make possible the formulation of discourse dissemination of science, technology and innovation. The analysis showed the coexistence of discourse science, discourse science journalism and discourse institutional promotion. From interdiscursive and intertextual relations, these fields alternate or overlap to fulfill hegemonic maintenance purposes, without significant attention to the educational dimension of science journalism.